Le ‘Gouffre du Colorado’ de Thomas Moran : Carrefour d’influences ou centre de diffusion ? - Wendy Harding; Jacky Martin (Anglophonia)
A work of art can be seen as a crossroads at which various historical movements converge, but it is also in motion, tracing its own trajectory. Drawing on actor-network theory, particularly as developed by Bruno Latour, this article situates Thomas Moran’s “The Chasm of the Colorado” (1873-74), in relation to contemporaneous events – notably Powell’s explorations of the Colorado River (1869; 1872) and Congress’s purchase of Moran’s painting (1874) – to show how it was taken up in the project of defining the territory of the young American republic. To become hegemonic, the territorial network in which the painting partakes had to fulfill the three functions of discovery, diffusion and potentiality. In other words, it had to come into existence, to become known, and to be rendered usable. The painting is one of the interconnected inscriptions that together create the Grand Canyon for the American public; among these are the heroic canyon, the pictorial canyon, and the strategic canyon. Finally the painting is not so much a singular object as a hybrid assemblage traversed by the various trajectories that bring it into existence and perpetuate it.